Theoretical modelling of dark energy in the universe - Sia, Wen Xuan (Nanyang Technological University, 2020)
This thesis serves as a pedagogical introduction for readers interested in understanding the nature and concept of dark energy. The basics of general relativity and cosmology will be excerpted for better understanding and 8 different classes of dark energy models will be introduced. This thesis starts with the discussion on certain general properties of dark energy followed by the evidence for the existence of dark energy. Next, it proceeds to discuss regarding the standard model of cosmology, the Λ-CDM model. Modified matter models such as quintessence, k-essence, coupled dark energy, chameleon scalar fields and unified dark energy are also studied in this thesis. In each dark energy model classification, general properties and constraints of each theory will be introduced along with a few representative models to further illustrate their positions and credibility in the field. In addition, local gravity constraints are also studied alongside with the introduction of modified gravity models such as f(R) gravity and scalar-tensor theories as an alternative to explain the current situation of the universe via the modification of gravitational laws. Ultimately, a summary of the properties of each model will be presented to conclude the thesis.